1981
DOI: 10.1002/art.1780240807
|View full text |Cite
|
Sign up to set email alerts
|

Procainamide‐lymphocyte reactions. a possible explanation for drug‐induced autoimmunity

Abstract: Procainamide therapy has been associated with a lupus erythematosus (LE) like illness. At least 50% of patients who take the drug for a long time develop antinuclear antibodies and approximately 10% of these develop the complete clinical syndrome (1-3). There has been considerable speculation about the pathogenesis of the drug-induced disease. Most theories implicate drugnucleoprotein interactions, which result in the induction of antinuclear antibodies, but these explanations do not account for other autoanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Similar findings have been reported with regard to discontinuation of procainamide treatment and the abrupt disappearance of lymphocytotoxic antibodies. The activity in all cases decreased after 3 to 1 6 weeks [15]. By contrast, IgG isotype anti-myeloperoxidase was found to persist at high concentrations, that were most pronounced after several years, despite clinical improvement.…”
Section: Discussionmentioning
confidence: 71%
“…Similar findings have been reported with regard to discontinuation of procainamide treatment and the abrupt disappearance of lymphocytotoxic antibodies. The activity in all cases decreased after 3 to 1 6 weeks [15]. By contrast, IgG isotype anti-myeloperoxidase was found to persist at high concentrations, that were most pronounced after several years, despite clinical improvement.…”
Section: Discussionmentioning
confidence: 71%
“…They proposed that antinucleic acid antibodies might appear in PA-treated patients as a consequence of a disorder of immune regulation resulting from a reaction between PA and lymphocyte membranes. In addition, this same group has reported that when PA was added to antigen-driven cultures of sheep erythrocyte-primed rabbit spleen cells, a prolonged antibody-forming cell response was observed (29). This experiment suggested that PA acted by altering suppressor T-cell circuits that may regulate this in vitro response.…”
Section: Tmitomentioning
confidence: 92%
“…Lymphocytotoxic antibodies have been reported in DRL secondary to procainamide, hydralazine and certain anticonvulsants (Bluestein et al 1981;Hughes et al 1987).…”
Section: Lymphocytotoxic Antibodiesmentioning
confidence: 99%